2018
DOI: 10.3390/ijerph15051020
|View full text |Cite
|
Sign up to set email alerts
|

Eating Alone is Differentially Associated with the Risk of Metabolic Syndrome in Korean Men and Women

Abstract: Few studies have examined overall patterns of eating alone in relation to the risk of metabolic syndrome (MetS) in Korean populations. The present study aimed to examine the relationship between patterns of eating alone and the risk of MetS in Korean adults. Data from the Korea National Health and Nutrition Examination Survey (KNHANES) for 2013–2015 were used, with 8988 Korean adult participants, including 3624 men and 5364 women, aged 18 to 64 years. Patterns of eating alone were categorized into eight groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 33 publications
0
7
0
3
Order By: Relevance
“…In previous studies, it was found that the sense of belonging as a community and a high level of social support promote physical and psychological health because they provides a sense of emotional stability in relationships among residents [ 23 ]. The finding that social support within the community affects the improvement of health outcomes (e.g., individual health level, well-being, and quality of life) are consistently supported by various studies [ 2 , 19 , 20 , 23 ]. In particular, the higher the level of emotional and informational support, the higher the confidence and competence in personal health management [ 23 , 42 , 55 ].…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In previous studies, it was found that the sense of belonging as a community and a high level of social support promote physical and psychological health because they provides a sense of emotional stability in relationships among residents [ 23 ]. The finding that social support within the community affects the improvement of health outcomes (e.g., individual health level, well-being, and quality of life) are consistently supported by various studies [ 2 , 19 , 20 , 23 ]. In particular, the higher the level of emotional and informational support, the higher the confidence and competence in personal health management [ 23 , 42 , 55 ].…”
Section: Discussionmentioning
confidence: 87%
“…It has also been reported that the risk of MetS increases when one’s socioeconomic level and educational level are low [ 8 , 14 ], when one smokes [ 15 ], frequently binge drinks [ 16 ], and does less physical activity [ 17 , 18 ]. Recent studies [ 19 – 23 ] have emphasized the importance of understanding both psychosocial factors and physical characteristics. In particular, it was found that emotional states such as stress and depression, health-related lifestyle habits such as regular exercise, and environmental factors such as social support also affect the prevalence of MetS.…”
Section: Introductionmentioning
confidence: 99%
“…No Brasil, há um aumento progressivo da quantidade de pessoas morando sozinhas, atingindo o número de 11,7 milhões de adultos em 2019, acompanhado pelo aprofundamento do processo de urbanização (IBGE, 2019). Tais processos têm sido explorados por parte da comunidade acadêmica a partir de hipóteses que o associam com o aumento do número de doenças de saúde mental, como aumento do estresse, sintomas depressivos (KIM, 2021;KWON et al, 2018;CHUNG;SHIN, 2018).…”
Section: Introductionunclassified
“…Some previous studies reported that eating alone was associated with various health problems. Eating alone was related to a reduced calorie intake and a less-varied diet 8,9 , and it could be a direct risk factor for Mets 10 .…”
Section: Introductionmentioning
confidence: 99%